Channel independent physical layer security - Ankaralı, Zekeriyya Esat; Yılmaz, Mustafa Harun; Hafez, Mohammed; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers Inc., 2016)
Security is one of the key requirements of wireless communication systems. By exploiting the broadcast nature of wireless medium, a malicious user might attempt to mislead the legitimate nodes, intercept the communication and overhear the private information. In order to combat against such malicious attacks, various encryption using security techniques have been proposed in the literature. Recently, physical layer (PHY) security has emerged as an additional countermeasure to the encryption based approaches and become very popular. Unlike cryptography, PHY security techniques target to protect the signal itself rather than encrypting the information bits. However, most of these techniques are designed based on specific channel conditions. Since channel has a random nature and cannot be controlled by users, such a design approach may remain unreliable for many practical scenarios where the desired channel state does not exist. Therefore, in this study, we highlight the importance of the channel independent PHY security techniques. In order to draft the ongoing efforts and provide the open issues in this direction, three different concepts are discussed along with the reviews of sample studies.
Keywords: Cyclostationarity; Directional Modulation; Intentional Interference; Physical Layer Security; Spatial Domain